A Framework for Visualization of Geographical Information Data using Vector Format - Syahrul Nizam, Junaini; Wang, Yin Chai; Jonathan, Sidi (Centre for Academic Information Services, UNIMAS, 2007)
The rapidly increasing era of Internet technology has created an infrastructure that ideally suited to the widespread distribution of geographical information. Since then, the rapid growth in number of geo-spatial applications has present new challenges for the development of more robust geo-information systems (GIS). This paper provides an insight and opportunity for integration of remote sensing, GIS and visualization technologies in a prototype of map application. The ability to present the geo-data in an easily understandable framework using interactive map is very important. In this paper we present the fundamental framework of visualization of geo map using vector data. Our proposed framework should be able to cope with the problem of large vector maps visualization over the Internet.